(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The main objective of this study was to determine the prevalence of Candida carriage among tobacco users and smokers along with in vitro evaluation of phospholipase and hemolysin activity of Candida albicans. Methods: A laboratory based cross-sectional study was carried out in Dharan Sub-Metropolitan city, Eastern Nepal from June 2018 to November 2018. During the study 150 oral rinse samples were obtained from smokers (50), smokeless tobacco consumers (50) and non-tobacco users (50) as control group. The participants were provided 10 ml of normal saline and were asked to oral rinse for 1 minute. Oral rinse was collected in a sterile screw capped container and was transported to microbiology laboratory by maintaining the cold chain. The oral rinse sample was inoculated onto the Sabouraud dextrose agar with chloramphenicol and was incubated at 37°C for 3-4 days. The number of colonies of Candida was counted and C. albicans were identified by cultural characteristics, staining, germ tube test and chlamydospore formation test. Results: The prevalence of Candida carriage was reported to be 22 (44%) in smoker group, 26 (52%) among smokeless tobacco users and 13 (26%) among control groups. The prevalence of Candida carriage was found to be significantly higher in the study group associated with tobacco chewers (P=0.008). However, the Candida carriage among smoker’s group was not found to be statistically significant (P=0.059). Isolation of Candida albicans was higher among smokeless tobacco users 15 (30%), smokers 5 (10%) and non-users 6 (12%). Conclusion: Colonization and carriage of Candida in the oral cavity of smokers and tobacco chewers were found to be higher than in controls. In addition, individuals with poor oral hygiene increase the risk of Candida colonization and infection under host debilitated condition.